Effect of WC on the joint of Ti(C, N)-based cermet/steel joint by autogenous pressure-assisted interlayer-free diffusion bonding. (July 2015) - Guo, Zhixing; Lian, Yi; Zhong, Hua; Xiong, Ji; Wan, Weicai
Abstract: Adherent joint of Ti(C, N)-based cermet and steel was achieved by a novel diffusion bonding method, which was free of external pressure and interlayer. The effect of WC content of the cermet on the microstructure and properties of the joint was investigated. The results showed that WC addition resulted in grain size decrease and formation of white core/black rim phase apart from conventional black core/gray rim microstructure. The joints appeared to consist of four bonding zones, i.e., binder-enriched surface layer (A), Fe–Ni bonded cermet layer (B), austenite layer (C) and martensite layer (D). The thickness of the bonding zones firstly increased after WC addition due to severe denitrification reaction and tighter contact of the base materials. The thickness slightly decreased after 15 wt.% WC addition since the dissolution and diffusion of Ti are inhibited by W and Mo. The gradient bonding zone structure mitigated the CTE mismatch of cermets and steel, and the maximum residual stress decreased with the increase of bonding zone thickness. The location of the maximum residual stress region transfers from the cermet side to the ductile austenite layer in the vicinity of steel, which relieves the residual stress by plastic deformation. The shear strength was also enhanced due to the decrease of residual stress and transition of the maximum residual stress region. Highlights: Novel joining method free of interlayer and external pressure is introduced. Joint consists of Ni-enriched surface, Fe–Ni bonded cermet, austenite and martensite. WC leads to the thickness increase of bonding zones due to severe N decomposition. Residual stress decreases and transfers from cermet side to ductile austenite layer. Strength is enhanced by residual stress decrease and austenite plastic deformation.